Shoulder injuries in elite rugby union football matches: Epidemiology and mechanisms. Issue 5 (September 2015) - Usman, Juliana; McIntosh, Andrew S.; Quarrie, Kenneth; Targett, Stephen
Abstract Objectives Shoulder injuries in rugby union football have been the focus of few in-depth studies, despite their frequency and severity. The study's objective was to describe the incidence, patterns and mechanisms of shoulder injuries in rugby. Design Prospective cohort study of shoulder injury incidence and retrospective case-series study of shoulder injury mechanisms. Methods Data were collected from Super Rugby matches from 2005 to 2010 involving elite level adult male rugby players. Results 7920 player participation hours and 100 shoulder injuries were recorded during 397 Super Rugby matches. The shoulder injury incidence rate was 13 per 1000 player hours (95% confidence interval 10–16). The mean number of days unavailable for selection due to these injuries was 37 (95% confidence interval 25–54). Tacklers sustained shoulder injuries at a higher rate than ball carriers (Rate Ratio = 1.7 (95% confidence interval 0.5–5.3)). The most frequently reported injuries were those to the acromio-clavicular joint; dislocations resulted in the greatest amount of missed play. Using video analysis, 47 of the 100 shoulder injury events were successfully identified and analyzed. The main mechanisms of shoulder injury were contact with the ground with the shoulder/arm in horizontal adduction, flexion, and internal rotation; and impact to the lateral aspect of the shoulder with the elbow flexed and arm at the side. Conclusions Direct impact to the shoulder, either through player-to-player contact or contact with the ground, is the main cause of shoulder injury. Methods to reduce injury risk, such as shoulder pads and tackle skills, require consideration.